Examining the trophic ecology of five myctophid genera in the southern Benguela using morphological, stomach content and stable isotope analyses - Maré, Charné (Department of Biological Sciences, 2023)
Myctophids, mesopelagic fishes commonly known as lanternfish, are a vital component of the oceanic food web. However, significant uncertainties about the feeding habits of co-occurring and potentially competing myctophid genera still exist. This study examined the trophic ecology of five genera of myctophid fishes from the southern Benguela, namely Diaphus spp., Gymnoscopelus spp., Lampanyctodes hectoris, Lampanyctus spp. and Symbolophorus spp. Fishes were collected during DFFE research surveys conducted in 2019 and were processed for morphological (M), stomach content (SC), and stable isotope (SI) analyses. The morphological analysis determined the relationship between gape and fish size for each genus and compared these between genera. The stomach content analysis evaluated the relative importance of prey items using percent frequency of occurrence (%F), percent numerical abundance (%N) and percentage contribution to dietary carbon (%C), and combined these into an index of relative importance (%IRI). Owing to the high concentration of lipids within the muscle tissue of myctophids, samples were run in duplicate (one lipidextracted and one untreated sample) to obtain accurate δ13C (to infer source production) and δ 15N (to infer trophic level) values. Significant linear relationships between gape and fish standard length (SL) were found for all genera, and average gape size relative to SL differed significantly between genera, with Symbolophorus spp. having the smallest and Lampanyctodes hectoris the largest values. Myctophids within the southern Benguela were generalist and opportunistic secondary and tertiary consumers. They consumed an array of macro- and meso-zooplankton with euphausiids being the principal prey item in terms of %IRI for all five genera. Significant differences in average prey length were observed between the genera and the positive sizerelated shift in average prey length noted for Symbolophorus spp. provided evidence of interand intrageneric dietary segregation. Although the differences in δ15N do not fully reflect the results obtained from the stomach content analysis, the hypothesis of inter- and intrageneric dietary segregation is further supported by Diaphus spp. and L. hectoris which both had significantly higher δ15N values compared to the other three genera, as well as by the positive (Diaphus spp., L. hectoris and Symbolophorus spp.), negative (Gymnoscopelus spp.) and nonsignificant (Lampanyctus spp.) size-related shifts in δ15N. Significant variation in δ13C values were found, with some genera showing complete segregation (e.g. Lampanyctus spp. and Symbolophorus spp.) or overlap (e.g. Diaphus spp., Gymnoscopelus spp. and Lampanyctus spp.) in their foraging habitats, resource use or source production. Furthermore, both positive (i.e. Diaphus spp. and L. hectoris) and negative (Gymnoscopelus spp.) size-related shifts in δ13C were observed, possibly indicating differential habitat use within each of these genera. However, the relationship between δ13C and SL for Diaphus spp. was significantly influenced by outliers, possibly indicating opportunistic feeding by some individuals. Myctophids are still largely understudied within this system. Therefore, despite the small sample size for each of the five genera, this study serves as a baseline for better understanding the role that these genera play within the southern Benguela food web. This knowledge is important for developing an ecosystem approach to fisheries management of mesopelagic fishes in the southern Benguela, should commercial exploitation of these resources begin as seems likely. Although the results of this study provide a glimpse into the trophic ecology of local myctophid genera, future studies should include increased sampling in terms of the numbers of individuals and genera examined and in spatial and temporal coverage through-out the entire southern Benguela.